Well-facilitated farmland improves nitrogen use efficiency and reduces environmental impacts in the Huang-Huai-Hai Region, China - Xiaoqing Wang; Wenjiao Shi; Qiangyi Yu; Xiangzheng Deng; Lijun Zuo; Xiaoli Shi; Minglei Wang; Jun Li (Journal of Integrative Agriculture, 2025)
The well-facilitated farmland projects (WFFPs) involve the typical sustainable intensification of farmland use and play a key role in raising food production in China. However, whether such WFFPs can enhance the nitrogen (N) use efficiency and reduce environmental impacts is still unclear. Here, we examined the data from 502 valid questionnaires collected from WFFPs in the major grain-producing area, the Huang-Huai-Hai Region (HHHR) in China, with 429 samples for wheat, 328 for maize, and 122 for rice. We identified gaps in N use efficiency (NUE) and N losses from the production of the three crops between the sampled WFFPs and counties based on the statistical data. The results showed that compared to the county-level (wheat, 39.1%; maize, 33.8%; rice, 35.1%), the NUEs for wheat (55.2%), maize (52.1%), and rice (50.2%) in the WFFPs were significantly improved (P<0.05). In addition, the intensities of ammonia (NH3) volatilization (9.9−12.2 kg N ha–1), N leaching (6.5−16.9 kg N ha–1), and nitrous oxide (N2O) emissions (1.2−1.6 kg N ha–1) from crop production in the sampled WFFPs were significantly lower than the county averages (P<0.05). Simulations showed that if the N rates are reduced by 10.0, 15.0, and 20.0% for the counties, the NUEs of wheat, maize, and rice in the HHHR will increase by 2.9−6.3, 2.4−5.2, and 2.6−5.7%, respectively. If the N rate is reduced to the WFFP level in each county, the NUEs of the three crops will increase by 12.9−19.5%, and the N leaching, NH3, and N2O emissions will be reduced by 48.9−56.2, 37.4−42.9, and 46.0−66.5%, respectively. Our findings highlight that efficient N management practices in sustainable intensive farmland have considerable potential for reducing environmental impacts.